2024
DOI: 10.1002/hbm.26553
|View full text |Cite
|
Sign up to set email alerts
|

Source‐based morphometry reveals structural brain pattern abnormalities in 22q11.2 deletion syndrome

Ruiyang Ge,
Christopher R. K. Ching,
Anne S. Bassett
et al.

Abstract: Abstract22q11.2 deletion syndrome (22q11DS) is the most frequently occurring microdeletion in humans. It is associated with a significant impact on brain structure, including prominent reductions in gray matter volume (GMV), and neuropsychiatric manifestations, including cognitive impairment and psychosis. It is unclear whether GMV alterations in 22q11DS occur according to distinct structural patterns. Then, 783 participants (470 with 22q11DS: 51% females, mean age [SD] 18.2 [9.2]; and 313 typically developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Global cerebellar volume has been widely found to be significantly impacted in 22q11.2DS, with a meta-analysis by Rogdaki et al [60] finding a large effect size (g = −1.25) in a sample of 147 subjects, and Schmitt et al [83] finding a mean 17.3% reduction in total cerebellar volume in 79 individuals with 22q11.2DS compared to TD. Similar analyses have been carried out by Ge et al [84], Tan et al [59], and Campbell et al [56], converging in their finding of global volumetric reductions in the cerebellum. Granular analyses of focal cerebellar deficits are more limited, though Schmitt et al [83] identified volumetric reductions along an anterior-posterior gradient such that regions of the superior posterior cerebellum, Crus I and II, as well as lobules VIIB and VIIIA, were disproportionately affected after controlling for total brain volumes [83].…”
Section: Cerebellumsupporting
confidence: 75%
“…Global cerebellar volume has been widely found to be significantly impacted in 22q11.2DS, with a meta-analysis by Rogdaki et al [60] finding a large effect size (g = −1.25) in a sample of 147 subjects, and Schmitt et al [83] finding a mean 17.3% reduction in total cerebellar volume in 79 individuals with 22q11.2DS compared to TD. Similar analyses have been carried out by Ge et al [84], Tan et al [59], and Campbell et al [56], converging in their finding of global volumetric reductions in the cerebellum. Granular analyses of focal cerebellar deficits are more limited, though Schmitt et al [83] identified volumetric reductions along an anterior-posterior gradient such that regions of the superior posterior cerebellum, Crus I and II, as well as lobules VIIB and VIIIA, were disproportionately affected after controlling for total brain volumes [83].…”
Section: Cerebellumsupporting
confidence: 75%
“…Neuropsychological findings include deficits in a wide range of cognitive functions, such as attention, executive functioning, and visuospatial processing [11,17,[19][20][21][22][23]. Correlates of cognitive and intellectual deficits have been attributed to volumetric alterations in patients with 22q11.2DS [24][25][26][27], as well as to the emergence of psychotic symptoms [18,28,29].…”
Section: Introductionmentioning
confidence: 99%